Catalytic Self-condensation of 5-Hydroxymethylfurfural over Modified Heteropolyacid - Gawade, Anil B.; Yadav, Ganapati D. (Current Catalysis, 2017)
Background: 5-Hydroxymethylfurfural (HMF) and its derivatives are versatile materials having tremendous applications in a variety of industries. One of the interesting derivatives of HMF, 5, 5' (oxy-bis (methylene)) bis-2-furfural (OBMF), has potential uses in polymer and pharmaceuticals. The synthesis of OBMF is mainly reported by using homogeneous catalyst and only a few reports are published by using heterogeneous catalyst. Herein, we synthesized OBMF efficiently from HMF using supported heteropolyacid catalyst 20% (w/w) Cs2.5H0.5PW12O40/K-10 (CDK). Methods: A wet impregnation method was employed for the preparation of CDK. Initially a dry K-10 was impregnated by aqueous solution of CsCl with vigorous stirring. Then it was dried at 150°C for 3 h and preformed material was again impregnated by a solution of DTP in methanol. Finally, it was well dried and calcined at 300°C for 3 h. All the catalysts were characterized by different techniques such as XRD, FTIR, ASAP, TPD and TGA. Effects of various kinetic parameters were studied to fix the reaction conditions. Reaction mechanism was predicted; and kinetic model was developed. Results: Among all the catalysts, CDK was found active, selective, and reusable catalyst for OBMF synthesis. The yield of OBMF was increased as water formed in reaction was removed by using Dean Stark apparatus. OBMF was efficiently obtained with 98% selectivity at HMF conversion of 95% over CDK. A second order kinetics was found to fit the data well. Conclusion: The strong acidic nature of CDK makes it an effective heterogeneous catalyst among sulfated zirconia and amberlyst- 15 for OBMF synthesis. It shows good reusability up to four cycles. Temperature, catalyst loading and mole of HMF were influencing the reaction rate. Maximum yield of OBMF can be obtained at following reaction conditions: temperature; 100ºC, amount of catalyst; 0.015 g mL-1, mole of HMF; 1.5 mmol. The kinetic model was successfully developed for the reaction and follows LHHW mechanism. The calculated activation energy was 10.7 kcal/mol.
Keywords: reusability